2018
DOI: 10.1021/acs.analchem.8b05010
|View full text |Cite
|
Sign up to set email alerts
|

AF4-UV-MALS-ICP-MS/MS, spICP-MS, and STEM-EDX for the Characterization of Metal-Containing Nanoparticles in Gas Condensates from Petroleum Hydrocarbon Samples

Abstract: The coupling of flow field flow fractionation (FlFFF) with ICP-MS/MS for the fractionation and analysis of natural nanoparticles in environmental samples is becoming more popular. However, the applicability of this technique to non-aqueous samples such as gas condensates from petroleum hydrocarbon samples has not been reported yet. In this study, an asymmetric flow-field flow fractionation (AF4) system coupled with UV and MALS detectors has been optimized to perform the fractionation of natural nanoparticles p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…Moreover, the relative less dense surface coating of the Te-NPs might cause the numerous unsaturated coordination sites on the NP surface to easily absorb or bond with the solvent molecules [63] . It is also possible that the aggregated NPs became unstable and broke down in the AF4 channel, as reported for mercury NPs by Ruhland et al [64]. spICP-MS measures the aggregates as one whole particle without breaking them up resulting in an apparent larger average particle radius (67 nm) ; with the highest standard deviation (±4.3) amongst the 4 techniques further suggesting that the Te-NPs were heterogeneously distributed and more polydisperse than the Se-NPs.…”
Section: Particle Sizing By Dynamic Light Scattering (Dls)mentioning
confidence: 83%
“…Moreover, the relative less dense surface coating of the Te-NPs might cause the numerous unsaturated coordination sites on the NP surface to easily absorb or bond with the solvent molecules [63] . It is also possible that the aggregated NPs became unstable and broke down in the AF4 channel, as reported for mercury NPs by Ruhland et al [64]. spICP-MS measures the aggregates as one whole particle without breaking them up resulting in an apparent larger average particle radius (67 nm) ; with the highest standard deviation (±4.3) amongst the 4 techniques further suggesting that the Te-NPs were heterogeneously distributed and more polydisperse than the Se-NPs.…”
Section: Particle Sizing By Dynamic Light Scattering (Dls)mentioning
confidence: 83%
“…393 Ruhland et al detected Hg-containing NPs dispersed in tetrahydrofuran that originate from gas condensates of petroleum hydrocarbon samples. 394 It was also demonstrated that inorganic gunshot residue contains NPs that can be analyzed by spICP-MS for forensic purposes. 395 Fine (sub-micron and nano) particles were dispersed and detected by spICP-MS from electronic cigarette aerosols 396 and paper printing and shredding process 397 as well.…”
Section: Methodology and Applicationsmentioning
confidence: 99%
“…Although EDS is frequently coupled to TEM or SEM in any analytical scenario, other techniques like electron diffraction and electron energy-loss spectroscopy have also been considered to obtain structural information. The use of transmission electron microscopes working in scanning mode (STEM), 83,90,100,126,148,193,259,260,262 with high-angle annular dark-field detection, 46,134,218 allows to obtain Z-contrast images that can also add information about the chemical composition of the nanoparticles. Even though XAS techniques do not provide information on nanoparticle morphology, they have also been considered in some works 166,182,185,187,226 because of the interest for improving the information about the composition of the nanoparticles in complex samples.…”
Section: Techniques Complementing Sp-icp-ms: Analytical Platformsmentioning
confidence: 99%